Effects of vaccination against respiratory pathogens on feed intake, metabolic, and inflammatory responses in beef heifers - Rodrigues, M. C. [UNESP] (2015)
The objective of this study was to evaluate intake, metabolic, inflammatory, and acute-phase responses in beef heifers vaccinated against pathogens that cause bovine respiratory disease (BRD). Eighteen weaned Angus heifers (initial BW 257 ± 3 kg; initial age 245 ± 2 d) were ranked by BW and allocated to 2 groups, which were assigned to 2 experiments of 7 d and the following treatments on d 1 of each experiment: 1) revaccinated against infectious bovine rhinotracheitis virus, parainfluenza-3 virus, bovine respiratory syncytial virus, bovine viral diarrhea Types 1 and 2 viruses, and Mannheimia haemolytica (VAC; 2 mL [s.c.]) and 2) receiving a 2-mL s.c. injection of 0.9% sterile saline (CON). The group receiving VAC in Exp. 1 was assigned to CON in Exp. 2 and vice versa. Heifers were weaned 21 d before Exp. 1, when they all received the first dose of the aforementioned vaccine. Heifers were maintained in individual pens and offered free-choice mixed alfalfa-grass hay and 3.5 kg/d (DM basis) of a corn-based supplement throughout the study. During Exp. 1, hay and concentrate intake were evaluated daily. During Exp. 2, blood samples were collected before (-2 and 0 h) and at 2, 4, 6, 8, 12, 16, 24, 36, 48, 60, 72, 96, 120, 144, and 168 h after treatment administration. In Exp. 1, treatment × day interactions were detected (P < 0.01) for forage intake and total DMI; these parameters were reduced (P ≤ 0.05) in VAC heifers compared with CON heifers on d 1 and 2 by an average of 1.7 and 0.8 kg (DM basis), respectively. In Exp. 2, mean serum tumor necrosis factor α (TNFα) concentration was greater (P = 0.05) in VAC heifers compared with CON heifers and treatment × hour interactions were detected for all plasma variables (P ≤ 0.02), whereas a similar tendency was detected (P = 0.09) for blood TNFα mRNA expression. Haptoglobin concentrations were greater (P ≤ 0.05) in VAC heifers compared with CON heifers from 16 to 120 h. Blood TNFα mRNA expression was greater (P = 0.05) in VAC heifers compared with CON heifers at 12 h. Cortisol concentrations were greater (P ≤ 0.05) in VAC heifers compared with CON heifers from 2 to 16 h. Insulin concentration was greater (P = 0.02) in VAC heifers compared with CON heifers at 2 h. Leptin concentrations were greater (P ≤ 0.05) in VAC heifers compared with CON heifers from 6 to 16 h. In conclusion, vaccinating beef heifers against BRD pathogens decreased forage intake and total DMI during the 2 d following vaccination in Exp. 1, which can be associated with transient metabolic, inflammatory, and acute-phase responses elicited by vaccination in Exp. 2.